PEMAHAMAN PARSIAL TERHADAP Q.S AL-MUJADALAH 58:11 (STUDI LIVING QURAN DI PAMEKASAN MADURA) - Affani, Syukron (SUHUF, 2018)
Understanding of the Koran is obtained through the stages of indirect interpretation. The Qur'an that lives in society is the Qur'an as a social value system embodied through secondary reading. The understanding of the Qur'an adopted by the community (living Quran) is generally influenced by the views of the 'ulama, the teachers, and influenced by the general trend. Q.S al-Mujâdalah (58): 11 is one of the most popular verses of the Qur'an. Not infrequently Q.S al-Mujâdalah (58): 11 cited as a decorative background stage educational events in various Islamic educational institutions either madrassas or boarding schools and became the jargon of the virtue of education. The popularity of Q.S al-Mujâdalah (58): 11 is interesting because it is more quoted in part or ultimate fragment of a verse in the form of jawâb without mentioning the verse part of the syarth. Consequently, the understanding of Q.S al-Mujâdalah (58): 11 is a partial understanding because it is understood cut off. This issue is evident from the results of research conducted on religious leaders in the Village Sentol Pademawu District Pamekasan. The nature of research in this paper is field research (field research) and research that is religious (religious research) with the qualitative-phenomenological type. The design will emphasize the discovery of the repeated symptoms observed as the subject of the study before drawing up conceptual conclusions. Broadly speaking, the flow of this research is first, induction. This process is done at the data collection and processing stage; second, interpretation. The interpretation process is limited to data qualification. While interpretation is widely conducted on field data analysis process and theoretical data; third, conceptualization. The follow-up of the interpretation process is the preparation of the concept of research results